ANALISIS PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA BENGKEL LAS SARIRA MELALUI KEPUASAN - Abigael Kiding Allo; Gabriella; Stepanus Sandy (CV. Adiba Aisha Amira, 2024)
The aim of this research is to test whether service quality and price perceptions influence purchasing decisions at Sarira welding workshop services through satisfaction. The sample in this study came from the respondent population, namely customers of the Sarira welding workshop. The research method used in this research is the associative method. The analytical instrument in this research is a path analysis instrument using SPSS. Based on the results of research and data analysis, it shows that service quality has no significant effect on purchasing decisions, price perception has no significant effect on purchasing decisions, satisfaction has a significant effect on purchasing decisions, service quality has no significant effect on satisfaction, price perception has a significant effect on satisfaction, service quality has no has a significant influence on purchasing decisions through satisfaction and price perception has a significant influence on purchasing decisions through satisfaction. Testing was carried out partially for each variable.